PELATIHAN MENULIS CERPEN BERWAWASAN MITIGASI BENCANA PANDEMI COVID-19 UNTUK GURU MATA PELAJARAN BAHASA INDONESIA - Liliani, Else; Wiyatmi, Wiyatmi; Yulianeta, Yulianeta; Budiyanto, Dwi; Kusmarwanti, Kusmarwanti (Dimasatra, 2021)
One of the creative and productive ways to deal with boredom and avoid stress during self-quarantine due to the COVID-19 pandemic is creative writing. The Indonesian Literature Study Program, Faculty of Language and Arts, Yogyakarta State University held a short story writing training activity with the insight of the COVID-19 pandemic for Indonesian language subject teachers. The benefits of this activity, among others, are expected to be a trauma healing for residents who are currently experiencing self-quarantine, a recreational and productive activity, as a medium for disseminating knowledge of pandemic disaster mitigation to the wider community. This activity was carried out online using the zoom meeting application and was attended by 44 teachers from various regions in Indonesia. Described in a qualitative descriptive manner, the training designed with an intensive mentoring model was considered capable of improving the participants' short story writing skills. The success in the implementation of this activity is not only influenced by technology and social support, but the enthusiasm of the participants to take part in the training activities as well as the human resources of resource persons who are competent in their fields.